(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: The smile appearance and final facial profile is often dramatic to individuals perception of the beautiful face and the position of the mandible is the characteristic of the patients inherent underlying bony pattern and is difficult to alter during treatment, so, it may be beneficial to consider the balance between the incisal inclination and different mandibular sagittal positions. The study aims to find out the preferable maxillary incisor inclination in the smile profile of a female subject with respect to altered mandibular positions and to elucidate whether the rater’s profession plays a role in assessment of optimally esthetic facial profiles. Methods: A smiling profile photograph of a female patient with average facial profile was altered artistically to obtain 3 different mandibular positions in decrements, normal and increments of 4 mm and in each positions the incisors inclinations have been altered to different positive and negative inclinations. A total of 37 evaluators including panel of Professionals and Non-professionals were asked to score each photograph using a Likert-type scale. Mann-Whitney and Kruskal–Wallis tests is done for statistical analysis. Results: In retruded mandible normal incisor inclination is favoured by the Professionals and +5˚ incisor inclination by the Non-professionals. In orthognathic mandible +5˚ of incisor inclination is favoured by Professionals and +10˚ by Non-professionals and in protruded mandible normal incisor inclination is favoured by Professionals and +10˚ by Non-professionals. Conclusions: There is a youthful quality of establishing a slight protrusive maxillary denture for a woman in cases of mandibular deficiency or excess.